2019
DOI: 10.3390/f10010031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anthropogenic Factors on the Diversity and Structure of a Dry Forest in the Central Part of the Tumbesian Region (Ecuador–Perú)

Abstract: The dry forest of southern Ecuador and northern Perú (called the Tumbesian region) is known for its high diversity, endemism, and healthy conservation state. Nevertheless, the forest is exposed to many threats linked with human activities. To understand the effects of these threats, which have not been appropriately assessed, we pose two questions: (a) What are the diversity and structural situations of the forest? (b) Are anthropogenic activities affecting the composition and structure of the forest? The asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
11
0
5
Order By: Relevance
“…The Fabaceae family is identified in most previous studies as the most important pollen source both in terms of the number of pollen morphotypes and their relative abundances (e.g., Ramalho et al 1990, Faria et al 2012, de Novais et al 2015). In the present study, these results are not unexpected as the three plant families are also the richest ones in the aboveground vegetation of our study area (Cueva-Ortíz et al 2019). In contrast, pollen morphotypes of the other families, such as Tiliaceae, Cunoniaceae, Polygonaceae, Muntingiaceae, Sterculiaceae, which were identified as primary foraging resources for both M. mimetica and Scaptotrigona sp.…”
Section: Discussionsupporting
confidence: 76%
“…The Fabaceae family is identified in most previous studies as the most important pollen source both in terms of the number of pollen morphotypes and their relative abundances (e.g., Ramalho et al 1990, Faria et al 2012, de Novais et al 2015). In the present study, these results are not unexpected as the three plant families are also the richest ones in the aboveground vegetation of our study area (Cueva-Ortíz et al 2019). In contrast, pollen morphotypes of the other families, such as Tiliaceae, Cunoniaceae, Polygonaceae, Muntingiaceae, Sterculiaceae, which were identified as primary foraging resources for both M. mimetica and Scaptotrigona sp.…”
Section: Discussionsupporting
confidence: 76%
“…overgrazed forests dominated by grazing‐resistant species in the understorey), formal studies on this subject are lacking. Recently, Cueva‐Ortiz et al () found that anthropogenic disturbances affect forest structure and diversity in the TDFs of southern Ecuador, but species traits were not part of their study. Future research on trait‐based filtering in response to anthropogenic threats would contribute to a better understanding of the importance of different traits in determining species’ sensitivities to these threats.…”
Section: Discussionmentioning
confidence: 96%
“…overgrazed forests dominated by grazing-resistant species in the understorey), formal studies on this subject are lacking. Recently, Cueva- Ortiz et al (2019) found that anthropogenic disturbances affect forest structure and diversity in the TDFs of southern Ecuador, but species traits were not part of their study.…”
Section: Improving Tree Species Vulnerability Assessmentsmentioning
confidence: 99%
“…In support of the first hypothesis, Phyllostomidae showed greater sensitivity to habitat disturbance compared to the understory community as a whole based on richness. The negative association between richness and disturbance for both groups was likely the result of reduced tree density in semi-natural and degraded forests compared to natural forest, caused by years of selective logging, agriculture, and livestock grazing 8 , 10 , 19 , 24 , 35 , 36 . Simplification of structural complexity can adversely affect the presence and abundance of bats by reducing their roosting sites, shelter and food availability 31 , 37 .…”
Section: Discussionmentioning
confidence: 99%